Customer feedback towards Islamic banking services: a case study at Klang, Selangor / Syarifah Hasmirah Syed Yunus and Anis Afiqah Abdullah Chik - Syed Yunus, Syarifah Hasmirah; Abdullah Chik, Anis Afiqah (2014)
The purpose of this thesis is to identify the awareness level of the customer of Islamic banking and the factors that influence their awareness. It is a comparison and association study that is to test whether or not one variable causes another to change. In this research, it aims to analyze whether the marketing and advertising, the availability of services, environment and religious value will influence the awareness level among the customer of Islamic banking. A word count of the past researches was utilized in addition to the study on the factors influencing the level of awareness. Cross sectional survey was used as a method to gather the data. Many conclusions were drawn based on the results of the research.